Natural Position Resources in Bach Long Vy Island - Thạnh, Trần Đức; An, Lê Đức (Vietnam Journal of Earth Sciences, 2013)
Bach Long Vy is a far coastal island, and alonely locates in the approximate centre  of  The Gulf of Tonkin. By those, it possess the unique location, becomes an border - outpost in the sea of North Vietnam, and possesses the great advantages for accepting important liabilitis; and realizing many obligations and interests for the purpose of ensuring national security, defense and sovereignty, protecting environment, and developing socio-economy. The combination of shape, size, slope and height of island; and its coastal depth are appropriate to preventing the strong wind and wave; favorable for accessing and building the infrastructure at the island, especially wharf  and anchorage sites for two wind seasons alternately. Small in area, but the island has fully responsibility for the functions of an administrative district in Vietnam. By the basic values and advantages on the spacial morphology and structure, and dynamic stability, the island has enough the conditions for considerable inhabitants, and sustainable socio-economic development.